ANALISIS MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMP - Nadya Rismawati; Gida Kadarisma (Departement of Mathematics Education, 2019)
Success in learning is influenced by learning motivation possessed by students. With the learning motivation students will be able to reach the maximum level in achieving a learning achievement. This can be seen from the results of the study of the effect of learning motivation on learning achievement carried out on 32 students of class VII of SMPN 4 Ngamprah as a sample. This research was conducted by giving questionnaires to students as samples. The results of the statistical calculation test using the SPSS 16.0 application showed that the reliability interpretation of the effect of learning motivation on mathematics learning achievement was 71.3%.